Otimização de algoritmos de decodificação de códigos de bloco por conjuntos de informação visando sua implementação em hardware - Gortan, Antonio (2011)
The purpose of this work is to undertake a theoretical analysis of the processes involved in soft-decision decoding of linear block codes using the information set approach aiming at an efficient hardware implementation in FPGAs (Field Programmable Gate Arrays). Accordingly, four contributions to this goal are presented: a modified version of the Dorsch algorithm, a set of algorithms to determine the most reliable candidates and to gauge their quantity according desired coding gain, approaching its performance to the maximum likelihood decoder, a hardware implementable version of the BGW (from the authors initials: Barros, Godoy e Wille) stop rule and the attainment of design criteria for the number of quantization intervals to apply.